REALITAS DAUGTHERHOOD DALAM NOVEL GADIS TANGSI KARYA SUPARTO BRATA - Ade Husnul Mawadah (LITERA, 2011)
This study aims to describe the daugterhood reality in Gadis Tangsi, a novel by Suparto Brata. The reality covers two aspects, i.e. (a) a relation pattern between a mother and her daughter, and (b) the construction of the child character’s identity in relation to the mother character. The data source was Gadis Tangsi, a novel by Suparto Brata. The data were collected through intensive reading and recording and were analyzed using the qualitative descriptive technique. The findings show that the dauhgterhood reality is apparent in the relation of Raminem – Teyi and that of Putri Parasi – Teyi. Teyi is a reflection of a young woman who tries to rebel against values in an army boarding house environment. She is much influenced by Raminem (her mother) and Putri Parasi. They directly form her identity. They inculcate ideology to make her a different girl from the rest in the environment. The relation between the mother and her daughter in this novel serves as a means of constructing Teyi’s identity.